Epidemiologia e caracterização molecular dos vírus Dengue circulantes no Rio Grande do Norte, 2013-2014 - Carvalho, Daise Maria Cunha de Sousa (2015)
Dengue is an acute infectious disease, usually transmitted by Aedes aegypti mosquitoes. The etiologic agents belong to the family Flaviviridae, genus Flavivirus, and occur as four antigenically related but distinct serotypes designated DENV-1, 2, 3, and 4. In Brazil, the disease represents a national public health problem. The purpose of the present study was to describe epidemiological aspects of dengue in the State of Rio Grande do Norte, from 2013 to 2014. A total of 483 blood or serum samples, collected from January 2013 to December 2014, were studied by RT-PCR for viral detection and typing. The infection was confirmed in 36.44% (176/483) of the cases studied. This study detected the circulation of three serotypes of dengue virus in Rio Grande do Norte, DENV-1, 2, and 4. The predominant serotype in 2013-2014 was the DENV-4, representing 83.51% (81/97) and 68.35% (54/79) of the positive cases, respectively. Regarding the spatial distribution, most of the cases occurred in Natal and Caicó, with 9.28% (9/97) and 18.99% (15/79), respectively. The months with the biggest viral circulation in RN were March 2013 and May 2014. The female gender was the most affected, representing 69.07% (67/97) in 2013 and 54.43% (43/79) in 2014. The most affected age groups were 21-30 years (2013) and 11-20 years (2014) with 25.77% (25/97) and 20.25% (16/79) positive cases, respectively. Phylogenetic analysis indicated that genotype V (DENV-1) and genotype II (DENV-4) circulated in the State. Our results provide information about the dynamics of DENV in the Rio Grande do Norte, important for the development of disease control strategies.